2018
DOI: 10.1080/21541264.2017.1416268
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the mold: structures of the RNA polymerase I transcription complex reveal a new path for initiation

Abstract: While structures of the RNA polymerase (Pol) II initiation complex have been resolved and extensively studied, the Pol I initiation complex remained elusive. Here, we review the recent structural analyses of the yeast Pol I transcription initiation complex that reveal several unique and unexpected Pol I-specific properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In Figure 1 (A), a model for a LUCA tRNAome is shown based on comparison of maps and the relatedness of encoded amino acids. Some of the LUCA tRNAome assignments are based on information in an accompanying paper [ 17 ]. The model for LUCA gives an indication of lineages that appear most conserved.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Figure 1 (A), a model for a LUCA tRNAome is shown based on comparison of maps and the relatedness of encoded amino acids. Some of the LUCA tRNAome assignments are based on information in an accompanying paper [ 17 ]. The model for LUCA gives an indication of lineages that appear most conserved.…”
Section: Resultsmentioning
confidence: 99%
“…IM2 , for instance, the lineage tRNA Ala /tRNA Val →tRNA Ile →tRNA Phe →tRNA Tyr is indicated. Based on amino acid relatedness and positions in the codon-anticodon table, however, tRNA Leu →tRNA Phe →tRNA Tyr might be a more reasonable model [ 17 ]. We posit that tRNA Asn may originally be derived from tRNA Asp , similar to tRNA Gln being apparently derived from tRNA Glu , as might be expected based on amino acid similarity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then found that this region has DNAbinding activity, and that mutagenesis of the helices, alone or in combination, inhibited DNA-binding by PAF53 1-222 , Interestingly, the structure of the linker has not always been clearly discerned in structures of Pol I (104), possibly due to dynamics in its interactions with core Pol I or the template. It has been proposed that the linker spans the active site cleft and may in fact play a role in the narrowing of the cleft in the process of proceeding from initiation to escape (104,112). We are determining the role of the HTH in transcription, e.g.…”
Section: As Shown Inmentioning
confidence: 99%